Review and update on the biology of coptotermes havilandi (Isoptera, Rhinotermitidae) - Costa-Leonardo, Ana Maria [UNESP]; Barsotti, Raquel C. [UNESP]; De Camargo-Dietrich, Célia Regina R. [UNESP] (My University, 1999)
The introduction of Coptotermes havilandi in Brazil and some aspects of its biology are reviewed. We also describe an aerial principal nest collected from the 15th floor of a high-rise building and its subsidiary nest collected from the 14th floor of the same building. The population of the principal nest consisted of one imaginal physogastric queen, one imaginal king, 20 nymphoid neotenics (14 females and 6 males), 188 nymphs, many workers, presoldiers, soldiers and larvae. The population of the subsidiary nest consisted of 32 nymphoid neotenics (all females), alates, 2 preneotenics, some larvae and nymphs, many workers, presoldiers and soldiers. These neotenics were larger than those found in the principal nest. No eggs were found in either nest. A morphometric analysis of the nymphs and nymphoids was carried out and the morphology of the neotenics and of the imaginai reproductives is described.